Confidence Bands for Survivor Function of Two Parameters Exponential Distribution under Double Type-II Censoring with Bootstrap Percentile - Akhmad Fauzy (Program Studi Statistika Unisba, 2009)
This paper describes existing methods and develops new methods for constructing confidence bandsfor survivor function of two parameters exponential distribution under double type-II censoring. Ourresults are built on extensions of previous work by [11] and Balakrishnan [1]. They use maximumlikelihood estimator to construct interval estimation under double type-II censoring. The confidencebands are developed for survivor function using the confidence region about survivor function. We willuse another method, known as the bootstrap percentile from [4]. This method gives shorterconfidence bands compared to the traditional method.